(untitled) (Agroindustrial Science, 2022)
The aim of this study was to evaluate the effect of the time of the year, the age of the mother and the month of lactation on the chemical composition of the colostrum and milk of the llama (Lama glama). The study was carried out at the Quimsachata Experimental Center of the INIA. 89 samples of colostrum were analyzed to determine the content of immunoglobulin G; Likewise, the chemical composition of 46 colostrum samples and 476 milk samples was determined. The content of IgG, fat, non-fat solids (NFS), protein, lactose, density, freezing point and minerals in the colostrum were: 37.43mg/mL; 2.78%; 31.42%; 12.07%; 17.68%; 1.13g/cm3; -1.05ºC and 0.40% respectively. The contents of fat, NFS, protein, lactose, density, freezing point and minerals in the milk were: 3.43%; 11.61%; 4.40%; 6.46%; 1.037g/cm3; -0.48ºC and 0.36% respectively. In conclusion, the time of year does not influence the chemical composition of milk; likewise, the age of the mother does not influence any of the chemical components of colostrum, nor does it influence most of the components of milk except minerals; meanwhile, the month of lactation influences most of the components of milk, except fat.